Assessment of disease‐specific knowledge in Australian children with inflammatory bowel disease and their parents. (21st April 2017) - Day, Andrew S; Mylvaganam, Gaithri; Shalloo, Nollaig; Clarkson, Cathy; Leach, Steven T; Lemberg, Daniel A
Abstract : Aims: Disease‐specific knowledge may influence disease outcome and quality of life in children with inflammatory bowel disease (IBD). This prospective study aimed to define IBD‐related knowledge in a group of Australian children with IBD and their parents using a validated measure of disease‐specific knowledge, the Inflammatory Bowel Disease Knowledge Inventory Device (IBD‐KID). Methods: Children (less than 18 years) diagnosed with IBD who were members of the Australian patient support organisation were identified. Each family was sent copies of the IBD‐KID. Children aged 10–18 years and all parents were asked to complete the IBD‐KID and to also provide demographic details and disease characteristics. Results: Replies were received from 196 families: 262 parents and 128 children completed questionnaires. Most children had a diagnosis of Crohn disease (65%) and 51% were male. Children diagnosed in the preceding 6 years scored higher than those with longer time since diagnosis. Parents had better scores in the IBD‐KID than the children ( P  < 0.0001). Overall, parents and children had poor understanding of key management issues for IBD (such as side effects of steroids), important outcomes (e.g. growth) and the use of complementary therapies. Conclusions: Consistent patterns of IBD‐related knowledge were noted in this large group of Australian children with IBD and their parents. Measurement of disease‐related knowledge with the IBD‐KID can identify gaps in understanding, thereby permitting focused educational activities. Although these knowledge gaps may impact upon outcomes, further prospective studies are now required to elucidate the relationships between enhanced knowledge and specific outcomes.